Tennis performance and the dominant arm strength velocity in male and female tennis players - Mavvidis, A. (Studies in Physical Culture and Tourism, 2008)
Strength velocity is one of important components in tennis. The study used three throw tests to assess in what way the serve velocity was related to the prospects of its development and the respective performance during particular tests. The research sample was composed of 26 tennis athletes (13 boys and 13 girls), aged 21 (+1.4) years, with more than four years of tennis experience. The correlation between the tests was assessed with the aid of Pearson correlation, and the differences between the sexes were measured with t-tests. The level of statistical significance was set at p<0.001. As for boys, the serve velocity was statistically most strongly correlated with the strength velocity of the dominant hand during the tennis ball throw and centrifuge ball throw tests. As for girls, there was no correlation between serve velocity and the three throw tests. The results of the study showed that the strength velocity of the dominant hand affected the serve velocity in boys and girls in a different way.